2008
DOI: 10.1002/anie.200801992
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed H/D Exchange at Vinyl Groups without Olefin Isomerization

Abstract: Making the switch: The title reaction represents a rare example of olefinic CH activation without olefin isomerization. The conditions are sufficiently mild so that functional groups such as ketones, esters, nitriles, amines, sulfides, and alcohols are tolerated. This selectivity is demonstrated by deuterium labeling of several complex molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Those which perform H/D exchange at alkene C-H bonds usually do so with competing and poorly controlled alkene isomerization [65][66][67][68][69][70][71]. A recent exception is an iridium catalyst which does not isomerize alkenes [71]. None of these catalysts appear to act selectively at allylic positions as would be predicted by Fig.…”
Section: Alkene Isomerization and Deuteration At Allylic Positionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Those which perform H/D exchange at alkene C-H bonds usually do so with competing and poorly controlled alkene isomerization [65][66][67][68][69][70][71]. A recent exception is an iridium catalyst which does not isomerize alkenes [71]. None of these catalysts appear to act selectively at allylic positions as would be predicted by Fig.…”
Section: Alkene Isomerization and Deuteration At Allylic Positionsmentioning
confidence: 94%
“…Of the many catalysts for H/D exchange, most are effective on arene and alkane C-H bonds [63,64]. Those which perform H/D exchange at alkene C-H bonds usually do so with competing and poorly controlled alkene isomerization [65][66][67][68][69][70][71]. A recent exception is an iridium catalyst which does not isomerize alkenes [71].…”
Section: Alkene Isomerization and Deuteration At Allylic Positionsmentioning
confidence: 99%
“…A classical way to start probing the reactivity of a new complex is the investigation of its H/D exchange reactions: such a longstanding approach in the study of C-H and H-H bond activation and reaction mechanisms [17][18][19][20][21][22][23][24] is being extended, given the renewed interest in catalytic C-H activation [25][26][27] and novel applications of deuterium tags in biocatalysis [28][29][30][31] and analytical chemistry [32,33], leading to the current renaissance of the topic [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…While reports on the H/D exchange at aromatic C(sp 2 )−H bonds have been described, effective strategies for the chemo‐selective deuteration of alkenes continue to be scarce (Scheme ). In this context, inspired by studies from Bergman and Tilley, Hartwig described an iridium pincer complex, that allowed for the selective H/D scrambling at alkenyl moieties without isomerization, exploiting C 6 D 6 as the deuterium source . In contrast, Grotjahn showed that allylic deuteration of alkenes was accomplished by a bifunctional imidazolylphosphine,, whereas Oro used NHC‐supported rhodium(III) hydride catalyst for the selective β‐deuteration of styrenes ,.…”
Section: Methodsmentioning
confidence: 99%